Analysis of mitochondrial-targeted antioxidant SkQ1 effectiveness on myocardial ischemia-reperfusion injury in a rat model: Focus on morphological and ultrastructural tissue study - E. A. Senokosova; E. A. Velikanova; R. A. Mukhamadiyarov; O. D. Sidorova; E. O. Krivkina; L. V. Antonova; E. V. Grigoriev (Фармация и фармакология (Пятигорск), 2025)
Mitochondrial-targeted antioxidant SkQ1 demonstrates a high efficiency in animal models and potentially can be used for minimizing postoperative complications in an on-pump open-heart surgery.The aim of study was to the assessment of preservation degree and changes in the isolated rat heart characterized by prolonged cardioplegic ischemia, under the condition of donation of different SkQ1concentrations.Material and methods. Isolated Langendorff-perfused rat hearts of Wistar line (n=15) were included in the presented study; the effectiveness of 12 ng/mL and 120 ng/mL of SkQ1 was analyzed. A biochemical analysis (superoxide dismutase 2 [SOD2], malondialdehyde [MDA], Troponin-I, heart-type fatty acid-binding protein [H-FABP]), a histological analysis of tissues (hematoxylin and eosin staining), scanning electron microscopy using backscattered electrons and immunofluorescence staining for cytochrome C and cytochrome P450 reductase were performed. The quantitative data were processed using GraphPad Prism 7 (Graph Pad Software, USA).Results. The optimal myocardial preservation was discovered while using 12 ng/mL of SkQ1: the lowest concentrations of MDA (49.5 [41.1; 58.9] mmol/g), Troponin-I (22.3 [20.3; 23.9] pg/mL) and H-FABP (0.8 [0.6; 16.0] ng/mL) were associated with extensive areas of tissues with preserved transverse dark and light bands and a moderate interstitial edema. Moreover, non-deformed mitochondria were located mainly between the contractile fibers. Cytochrome C immunofluorescence was distributed locally, the luminescence intensity was 40% higher compared to the control group (p <0.0001). Increasing SkQ1 concentration to 120 ng/mL contributed to the aggravation of oxidative stress: MDA (63.8 [62.5; 83.0] mmol/g) and H-FABP (12.8 [4.1; 15.3] ng/mL) concentrations were closer to the control group values. Myocardial tissue in this group was characterized by a pronounced edema and a fragmentation of muscle fibers. There were signs of cardiomyocyte decay, myocytolysis and an intracellular edema. Cytochrome C was distributed evenly.Conclusion. 12 ng/mL of SkQ1 demonstrates pronounced antioxidant effects in the ischemic myocardium leading to a higher degree preservation of the heart muscle compared to 120 ng/mL of SkQ1 that was associated with an aggravated oxidative stress and structural changes of the tissue.